Effects of Stricter Environmental Regulations on Resource Development - Ian A. Lange; Michael Redlinger (Center for Economic Studies and ifo Institute (CESifo), 2018)
This analysis seeks to understand whether changes in oil regulation brought about by the shale revolution have restricted the pace of drilling and production. This hypothesis is tested using data on North Dakota and Montana both before and after North Dakota increased the level of bonding required. Results generally find that the new regulations had no statistical impact on the pace of drilling and production, however it is found that smaller operators reduced their production and exited. These results are instructive for policymakers who weigh the loss of economic welfare against improved environmental quality when deciding on new regulations.
Keywords: L51; L71; Q35; Q53; 330; oil and gas regulation; shale oil; drilling; firm exit